Answer:
![x^2 - 12x + 36 = (x-6)(x-6) = (x-6)^2](https://img.qammunity.org/2019/formulas/mathematics/high-school/4u0d4obskdcdoe40312eetshg970wzdu9o.png)
Explanation:
We are given the following expression:
![x^2 - 12x + 36](https://img.qammunity.org/2019/formulas/mathematics/high-school/534jn88gz0rf36vvkx4u18qvb78xbc712h.png)
We need to factor the given expression.
We will do this with the help of technique of splitting the middle term.
Factorization can be done as:
![x^2-12x + 36\\=x^2 - 6x-6x+36\\=x(x-6)-6(x-6)\\=(x-6)(x-6)\\=(x-6)^2](https://img.qammunity.org/2019/formulas/mathematics/high-school/8z29hqb3capvdrvnncn1jgjonyyux5gavf.png)
Thus, the factored form of given expression is:
![x^2 - 12x + 36 = (x-6)(x-6) = (x-6)^2](https://img.qammunity.org/2019/formulas/mathematics/high-school/4u0d4obskdcdoe40312eetshg970wzdu9o.png)